Penggunaan model problem based learning berbantuan media manipulatif untuk meningkatkan pemahaman konsep matematis pada siswa kelas IV SD - Nikita Novianti; Sukma Murni; Febri Restu Widianto (COLLASE (Creative of Learning Students Elementary Education), 2026)
This study is based on the background based on the problems that occur, namely the low ability to understand mathematical concepts in class IV students and some teachers still apply learning models that only provide material with the lecture method. The purpose of this study was to determine the use of the Problem Based Learning model to improve the ability to understand mathematical concepts at the elementary school level. Based on the background of the problem, the solution that can overcome the problems that occur at SDN 197 Karang Taruna Karangsari by using the Problem Based Learning model. The mix method research method was used for this research. The design used is squential explanatory. In qualitative research using quasi experimental methods with Nonrandomized Pre-test Post-test Control Group Design design. A total of 30 students in class IV A in the experimental class and 38 students in class IV B as the control class at SDN 197 Karang Taruna Karangsari. The results of the study based on statistical tests of the average gain value in the experimental class of 0.60 including the medium category and the average gain value of the control class obtained a result of 0.48 in the low category. This means that the Problem Based Learning model is better than using conventional models. Students are very enthusiastic about learning by using the Problem Based Learning model and this model is suitable for use in grade IV elementary school level.